Efficacy evaluation of fungus Syncephalastrum racemosum and nematicide avermectin against the root-knot nematode Meloidogyne incognita on cucumber. - Wen-Kun Huang; Jian-Hua Sun; Jiang-Kuan Cui; Gang-Feng Wang; Ling-An Kong; Huan Peng; Shu-Long Chen; De-Liang Peng (PLoS ONE)
The root-knot nematode (RKN) is one of the most damaging agricultural pests.Effective biological control is need for controlling this destructive pathogen in organic farming system. During October 2010 to 2011, the nematicidal effects of the Syncephalastrum racemosum fungus and the nematicide, avermectin, alone or combined were tested against the RKN (Meloidogyne incognita) on cucumber under pot and field condition in China. Under pot conditions, the application of S. racemosum alone or combined with avermectin significantly increased the plant vigor index by 31.4% and 10.9%, respectively compared to the M. incognita-inoculated control. However, treatment with avermectin alone did not significantly affect the plant vigor index. All treatments reduced the number of root galls and juvenile nematodes compared to the untreated control. Under greenhouse conditions, all treatments reduced the disease severity and enhanced fruit yield compared to the untreated control. Fewer nematodes infecting plant roots were observed after treatment with avermectin alone, S. racemosum alone or their combination compared to the M. incognita-inoculated control. Among all the treatments, application of avermectin or S. racemosum combined with avermectin was more effective than the S. racemosum treatment. Our results showed that application of S. racemosum combined with avermectin not only reduced the nematode number and plant disease severity but also enhanced plant vigor and yield. The results indicated that the combination of S. racemosum with avermectin could be an effective biological component in integrated management of RKN on cucumber.